UPAYA MENINGKATKAN KEMAMPUAN SISWA MENULIS KARANGAN NARASI MELALUI METODE PENEMUAN - Nursari Rindu Simanullang (KOHESI : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research was conducted in the even semester of 2022. The subjects of this research were 34 students in class XI-MIA Dahlia SMA Negeri 1 Telukdalam. This research was conducted in two cycles with implementation procedures: (1) planning, (2) action, (3) observation, (4) reflection. The research instruments used in the data collection process were observation sheets used as qualitative data sources and tests used as quantitative data sources. Based on the results of this study it was concluded that the application of the discovery method could increase the ability to write essays students play an active role during the learning process of writing narrative essays in cycle I the average value was 51.32 with a percentage of 20.58% while cycle II the average value was 80 with a percentage of 88 .24% have fulfilled the KKM at SMA Negeri 1 Telukdalam 2021/2022 Academic Year. Based on the results of the study, it is suggested (1) that Indonesian language teachers in class XI-MIA Dahlia at SMA Negeri 1 Telukdalam can use the research method as a source of information to determine students' abilities in the learning process, and (2) for students at SMA Negeri 1 Telukdalam to find out how far which abilities they have in the learning process.